2018
DOI: 10.3390/ijms19113293
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Function in Mammalian Spermatozoa

Abstract: AMP-activated protein kinase AMPK regulates cellular energy by controlling metabolism through the inhibition of anabolic pathways and the simultaneous stimulation of catabolic pathways. Given its central regulator role in cell metabolism, AMPK activity and its regulation have been the focus of relevant investigations, although only a few studies have focused on the AMPK function in the control of spermatozoa’s ability to fertilize. This review summarizes the known cellular roles of AMPK that have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 120 publications
0
43
0
1
Order By: Relevance
“…AMPK can be activated by physiological conditions, metabolic hormones and pharmacological molecules (Martin-Hidalgo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK can be activated by physiological conditions, metabolic hormones and pharmacological molecules (Martin-Hidalgo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is a cellular metabolism energy sensor and a key signalling kinase in spermatozoa (Nguyen et al, 2016). AMPK controls metabolism by inhibiting anabolic pathways and simultaneously stimulating catabolic pathways, thereby regulating cellular energy (Martin-Hidalgo et al, 2018). The regulation of AMPK activity could be an interesting tool with which to optimize animal sperm preservation methods.…”
mentioning
confidence: 99%
“…At this time, spermatozoa have already lost corresponding organelles to allow transcription and translation of genes, so the acquisition of these physiological abilities must rely on the modification of existing proteins (Castillo et al, 2019). AMPK and its phosphorylated form are expressed in a variety of mammalian sperm and mainly localized at the acrosome and at the mid-piece of flagellum (Martin-Hidalgo et al, 2018). Spermatozoa motility depends on flagellum beating, and mitochondria exist in the middle of the flagellum to provide energy for the movement (Gu et al, 2019).…”
Section: The Function Of Ampk In Spermatogenesismentioning
confidence: 99%
“…In boar and mouse semen, Zhao et al [60] found that Na 2 S, a fast H 2 S releasing donor, decreases sperm motility by disrupting multiple signaling pathways, which mainly include: decreased ATPase activity, inhibition of Akt, and activation of the adenosine 5'-monophosphate-activated protein kinase (AMPK) and phosphatase and tensin homologue (PTEN) pathways. The AMPK pathway affects spermatogenesis and performs a crucial role in sperm metabolism and the motility of various mammalian species (e.g., rats, stallions, humans) [61]. On the other hand, the activation of the PI3K/Akt pathway can help to counteract the effects of oxidative stress.…”
Section: Mechanisms Of Action Of H 2 S In Spermatozoamentioning
confidence: 99%